Soaring Towards Excellence / Institute of Research, Development and Commercialisation (IRDC), UiTM - UiTM, Institute of Research, Development and Commercialisation (IRDC) (Institute of Research, Development and Commercialisation (IRDC), UiTM, 2005)
Universiti Teknologi MARA's research and consultancy centre, Institute of Research, Development and Commercialisation, is the primary point of contact for industry, commerce and goverment bodies seeking to access the University's expertise. It was originally known as the Centre for Planning, Research and Development and was established in April 1980. In September 1987, due to it's growing importance and increasing number of research and consultancy activities in UiTM, the centre was restructured and branched into two divisions: the Research and Consultancy Centre (RACC), and the Planning and Evaluation Unit. The centre changed its name again to Bureau of Research and Consultancy (BRC) in 1994. BRC envolved to Institute of Research, Developement and Commercialisation (IRDC) after merging with Institute of Intellectual Property on 15 July 2003. IRDC supports the university's academic community through servicing their IRDC research, consultancy, intellectual property protection and commercialisation. Currently, the Institute is divided into six division.